PERAN DINAS SOSIAL KOTA PEKANBARU DALAM PENANGGULANGAN KEMSIKINAN UNTUK MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) TAHUN 2023 - Sinurat, Ruth Evinora; Wasillah, Asiah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Poverty is an issue that attracts significant attention as it relates to various aspects of life, such as the quality of life of individuals. As one of the goals of the Sustainable Development Goals (SDGs), namely